Enhancing Clinical Confidence: Effects of Medical Screening and Differential Diagnosis Training for Low Back Pain - Shavit R; Kushnir T; Nudelman Y; Springer S (Journal of Multidisciplinary Healthcare)
Ron Shavit,1 Talma Kushnir,2,3 Yaniv Nudelman,4,5 Shmuel Springer1 1The Neuromuscular & Human Performance Laboratory, Department of Physical Therapy, Faculty of Health Sciences, Ariel University, Ariel, Israel; 2Department of Psychology, Ariel University, Ariel, Israel; 3Adelson School of Medicine, Ariel University, Ariel, Israel; 4Department of Physical Therapy, Ariel University, Ariel, Israel; 5Maccabi Healthcare Services, Tel-Aviv, IsraelCorrespondence: Shmuel Springer, The Neuromuscular & Human Performance Laboratory, Department of Physical Therapy, Ariel University, Ariel University, Ariel, Israel, Tel +972-584572869, Email Shmuels@ariel.ac.ilPurpose: Direct access to physical therapy (PT) requires PTs to act as primary care providers, making differential diagnosis a critical component of patient assessment. We investigated how participation in postgraduate training in differential diagnosis and medical screening influences PTs’ confidence, self-efficacy, attitudes and beliefs about treating patients with low back pain (LBP).Patients and Methods: This prospective, two-arm study involved 49 PTs in an intervention group and 70 in a control group. The intervention included 40-hours of training on medical screening and differential diagnosis, focusing on red flags, clinical reasoning and referral pathways, while the control group received no intervention. Clinical confidence, self-efficacy, attitudes and beliefs were measured before, immediately after, and 6-months after training. Outcomes included the Primary Care Confidence Scale (PCCS), which assesses confidence in primary care practice, detection of serious pathology, and medical screening; the Physiotherapy Self-Efficacy (PSE) questionnaire, evaluating clinical self-efficacy in assessing and treating patients with LBP; and the Attitudes to Back Pain Scale for Musculoskeletal Practitioners (ABS-mp), which measures clinicians’ attitudes and beliefs about LBP.Results: The intervention group showed significant immediate improvements in PCCS scores (40.26 ± 5.23 to 45.24 ± 4.20, Cohen’s d = 1.08, p < 0.001) and PSE scores (51.06 ± 6.46 to 54.65 ± 5.78, Cohen’s d = 0.6, p < 0.001). At six-month, significant interaction effects were observed for PCCS (F = 17.49, Partial η² = 0.131, p < 0.001) and PSE scores (F = 5.87, Partial η² = 0.06, p < 0.05) and PSE scores (55.32 ± 6.09, p < 0.05), with the intervention group maintaining improvements while the control group showed no significant changes. No significant changes were observed in ABS-mp scores.Conclusion: This study highlights the positive impact of training in medical screening and differential diagnosis on reducing concerns and increasing clinical confidence and self-efficacy.Keywords: primary care, confidence, self-efficacy